The Correlations and Soil Properties Analysis of Temerloh, Pahang - Muzamir, Hasan; Amizatulhani, Abdullah; Aminaton, Marto (Malaysian Technical Universities Network (MTUN), 2010)

(untitled)
The characteristics of silty clay soil are different compared to other soils due to their low strength and high compressibility. It is also difficult to get an undisturbed sample for this type of soil for laboratory testing. Hence, the correlation between basic properties and depth or between basic properties itself will be useful to engineers especially for preliminary design purposes. An attempt was made to correlate the Atterberg limits itself and Atterberg limits with depth. In general, the correlations show that the liquid limit and plasticity index increase with the moisture content. The plasticity index also tends to increase with liquid limit. An attempt was also made to get correlation between the liquid limit with the clay/silt content. It is found that the liquid limit increases with the increase of clay/silt content, probably due to the clay particles tend to pull or absorb water to the surface of soil particle, making the liquid limit to be much higher. The results give an alternative for engineers to use the basic soil properties to predict the strength of soil. One can also determine the shear strength of the soil at certain depth below ground level. This will allows a quick and economic design for construction on clay.